الأعیاد والولائم في إندونیسیاأحكامھا وآدابھا في الفقھ الإسلاميقدمت هذه الرسالة لتكملة شروط الحصول على شهادة الماجستير في الشريعةالإسلاميةHoliday and wedding party in Indonesia, law and courtesiesin review of Islamic fiqih - Khozin, M.Nur; , Dr. M. Muinudinillah Basri, M.A; , Dr. M. Abdul Kholiq Hasan, M.A., M.Ed (2014)
Amounts of holiday and wedding party in Indonesia that was removing and growing to cause difference perspectives of ulama in punishing and construing it. Make the reason to write it in this thesis, with the purpose knowing of law and courtesies related with holiday and wedding party. This thesis used direct analysis method to the people and literation of library with compared the oldest and contemporary ulama's opinions in all of problem, before out of result that choose and strong. And this thesis was till at the conclusion that holiday there was in Indonesia, considerate from Islamic law divided into three sides, which are agreedable to, disagreed able to and agreed unable to. Among of important matter in this thesis is discussion about law and courtesies in holiday and wedding party and explanation how to construe the difference inside, completed with the deflections there were it, and solution for Indonesian people in this problem.